Linking Mother and Youth Parenting Attitudes: Indirect Effects via Maltreatment, Parent Involvement, and Youth Functioning - Thompson, Richard (Child Maltreat, 2014)
Evidence suggests that parenting attitudes are transmitted within families. However, limited research has examined this prospectively. The current prospective study examined direct effects of early maternal attitudes toward parenting (as measured at child age 4 by the Adult-Adolescent Parenting Inventory [AAPI]) on later youth parenting attitudes (as measured by the AAPI at youth age 18). Indirect effects via child maltreatment (physical abuse, sexual abuse, neglect, and emotional maltreatment), parent involvement, and youth functioning (internalizing and externalizing problems) were also assessed. Analyses were conducted on data from 412 families enrolled in the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN). There were significant direct effects for three of the four classes of mother parenting attitudes (appropriate developmental expectations of children, empathy toward children, and appropriate family roles) on youth attitudes but not for rejection of punishment. In addition, the following indirect effects were obtained: Mother expectations influenced youth expectations via neglect; mother empathy influenced youth empathy via both parental involvement and youth externalizing problems; and mother rejection of punishment influenced youth rejection of punishment via youth internalizing problems. None of the child or family process variables, however, affected the link between mother and youth attitudes about roles.